Imperfect bipolarity: The ‘third power’ factor in Soviet-American relations in the nuclear field (1958–1968) - V. А. Veselov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2023)
30 years after the end of the Cold War, bipolar structure still dominates in the nuclear sphere, although certain nuclear powers are closing the gap with Russia and the United States in terms of strategic arsenals and the system of world politics in general is moving towards polycentrism. At the same time, as US-Russian relations continue to deteriorate against the backdrop of the ‘Ukrainian crisis’, the prospects for strategic dialogue after the expiration of the Treaty on Measures for the Further Reduction and Limitation of Strategic Offensive Arms (New START) are becoming increasingly vague. The absence of a new agreement in this field threatens to throw international relations back to the beginning of the Cold War, with all the ensuing consequences. To avoid such a scenario, not only the leaders of Russia and the United States should demonstrate political will, but other nuclear powers should also be included in the negotiation process, particularly China. In this regard, the history of the Cold War can provide valuable lessons. The author argues that bipolarity (even at its apex in the late 1950s — early 1970s) had never been an exclusive characteristic of international relations. On the basis of a number of historical cases, the paper demonstrates that during this period the superpowers constantly had to reckon with the ‘third power’ factor. The latter did not only influence the logic and dynamics of Soviet-American relations, but also to a large extent predetermined the direction and nature of their military development and planning. Indeed, it was the ‘third power’ factor, namely China, along with the achievement of strategic parity between the superpowers that became one of the main impulses to the establishment of the non-proliferation regime. In conclusion, the author focuses on yet another important lesson from the Cold War: the experience of arms control negotiations during that period suggests that the meetings of politicians should be preceded by joint brainstorming sessions with scholars from interested countries. In the current situation, representatives of the academic community should take the lead so that by the time the political climate eventually changes, there would already be coherent and viable options for nuclear arms control adapted to new realities.